2017
DOI: 10.1177/0271678x17691784
|View full text |Cite
|
Sign up to set email alerts
|

Image-derived input function estimation on a TOF-enabled PET/MR for cerebral blood flow mapping

Abstract: O-HO PET imaging is an accurate method to measure cerebral blood flow (CBF) but it requires an arterial input function (AIF). Historically, image-derived AIF estimation suffers from low temporal resolution, spill-in, and spill-over problems. Here, we optimized tracer dose on a time-of-flight PET/MR according to the acquisition-specific noise-equivalent count rate curve. An optimized dose of 850 MBq of O-HO was determined, which allowed sufficient counts to reconstruct a short time-frame PET angiogram (PETA) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 37 publications
0
44
0
1
Order By: Relevance
“…However in PET studies of the brain, calculation of the IDIF is challenged by two factors: PVE [231,232] due to the small size of the blood pools, and subject motion [232,233]. Various approaches have been proposed to extract an accurate IDIF that can be classified into PET-only based methods [232,[234][235][236][237][238][239][240][241][242][243][244], stand-alone PET and MR-based methods [228,245,246], and fully-integrated PET/MR-based methods [247][248][249]. Combined PET/MR can potentially allow researchers to address the aforementioned challenges (PVE and subject motion) in an automatic way [228,248,249], in addition to bearing a logistic advantage.…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…However in PET studies of the brain, calculation of the IDIF is challenged by two factors: PVE [231,232] due to the small size of the blood pools, and subject motion [232,233]. Various approaches have been proposed to extract an accurate IDIF that can be classified into PET-only based methods [232,[234][235][236][237][238][239][240][241][242][243][244], stand-alone PET and MR-based methods [228,245,246], and fully-integrated PET/MR-based methods [247][248][249]. Combined PET/MR can potentially allow researchers to address the aforementioned challenges (PVE and subject motion) in an automatic way [228,248,249], in addition to bearing a logistic advantage.…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…MRI data could be used to assist and complement PET data in several ways [188]. Using TOF MR angiography can improve the delineation of the arterial volume in PET [184,[189][190][191]. The IDIF could be implemented in an automated pipeline to provide absolute values of cerebral glucose metabolism in a clinically feasible manner [192].…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%
“…To obviate the need for the arterial input function (AIF) in brain studies, several methodologies have been proposed to extract an image-derived input function (IDIF) directly from PET images (4)(5)(6)(7)(8)(9)(10)(11)(12). These studies demonstrated that the extraction of an IDIF from a dynamic PET dataset requires 3 main tasks: the accurate definition of a blood-pool region, the accurate correction for subject motion, and the exact correction of extracted time-activity curves for partial-volume effects because of the small diameter of the internal carotid arteries.…”
mentioning
confidence: 99%